INDONESIAN NURSES CULTURAL COMPETENCE: THE DEVELOPMENT AND PILOT TESTING OF INSTRUMENT - Tappy, Yunita Peggy (Klabat Journal of Nursing, 2024)
Introduction: This paper outlines the development and validation of the Indonesian Nurse's Cultural Competency Scale (IPNCCS) in response to the absence of such instrument for Indonesian nurses. Purpose: The aim was to create an instrument that accurately measures cultural competence among Indonesian nurses. Methods: The study followed a methodological approach in two phases, beginning with item generation through literature review, expert evaluation, and pilot testing with a sample of 50 Indonesian nurses. Result: Through item analysis, the scale's construct validity and reliability were established. The final scale comprises 46 items across five dimensions, showing strong internal consistency reliability (overall Cronbach’s alpha of .942, dimension Cronbach’s alpha ranging from .792 to .918), content validity, and construct validity. In conclusion, the INCCS offers a reliable and valid tool for assessing professional nurse competencies within diverse clinical settings in Indonesia. KEYWORDS: Competence, Cultural competency, Indonesian nurse, Nursing, Reliability, Validity